Increasing Application for Marriage Dispensation during the COVID-19 Pandemic in the Sociology Review of Law at the Jombang Religious Court - Rahayu Hartini; Jamik Imam Utomo (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2021)
This paper discusses the increasing application for Marriage Dispensation during the corona virus pandemic which is viewed from the sociological aspect of law. Applications for dispensation for marriage are more complicated and must be submitted through the Religious Courts, but the facts on the ground show that the number of applications for dispensation for marriage is increasing during this pandemic. The situation during this pandemic which makes sociological factors, the occurrence of imbalances in the structure of society makes the dysfunction of the community's inability to maintain their nature. The legal issues are: (1) What are the factors that increase the number of applications for a marriage dispensation in the Jombang Religious Courts (2) What are the considerations of the Jombang Religious Court judges in granting the marriage dispensation. This research is juridical and sociological in Jombang Religious Court. By using a statue approach, conceptual, with primary and secondary data types and analyzed descriptively qualitatively. The discussion of the research results shows that: 1). The increasing application for Marriage Dispensation during this pandemic is caused by the association of children with restrictions on learning activities so that their time is used more for playing gadgets that are not common and the lack of parental supervision, this makes many factors that can plunge them. 2). The basis of the judge's consideration in granting the application for dispensation for marriage is based on